Sea gravimeter system of the icebreaker `SHIRASE' - Segawa, Jiro; Kaminuma, Katsutada; Ueda, Yoshio (1984)
P(論文) The gravimeter system of the SHIRASE is the NIPRORI-1 sea gravimeter which was transferred from the icebreaker FUJI. In installing this gravimeter on the SHIRASE some changes for adaptation as well as some improvements for enhancing the capabilities were made. The main differences of the gravimeter installed on the SHIRASE are as follows : 1) The gravity sensor unit and the data processing unit were installed in separate rooms. 2) An air-cushioned board was placed in the gravity sensor room in order to reduce vibration of the floor caused by the engines. 3) The data processing unit was expanded, and computers and floppy disks were doubled. 4) Temperature regulation of the gravimeter was improved, so that it became possible to detect the tidal variation of gravity by the use of the existent gravity sensor. 5) Software for data processing was improved in two points; one concerned with the operation by interrogation and the other with the refinement of noise filtering. departmental bulletin paper